2014
DOI: 10.1016/j.lwt.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of protein isolated from defatted cashew nut shell: Influence of pH and NaCl on solubility and functional properties

Abstract: This work reports the isolation of protein from defatted cashew nut shell (CNS), with the crude protein product containing 91.07% protein. Under its natural conditions, the solubility of this protein isolate is comparable (74.02%) to that of mustard green meal protein. The solubility of the protein isolate decreases with decreasing pH, with the minimum solubility observed at its isoelectric point (pH 3). The water holding capacity, oil holding capacity, foaming capacity, foam stability, emulsifying capacity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 32 publications
8
58
0
Order By: Relevance
“…The highest WAC values were found at pH 2 (3.01 cm 3 H 2 O/g protein) and pH 10 (1.71 cm 3 H 2 O/g protein). At neutral pH, WAC was equal to 1.68 cm 3 H 2 O/g protein, higher than that of L. angustifolius protein isolates (0.24 to 0.45 cm 3 H 2 O/g protein) (Lqari et al, 2002) and lower than that of protein isolated from defatted cashew nut shell (2.56 cm 3 H 2 O/g protein) (Yuliana et al, 2014). WAC is an index of the ability of proteins to absorb and retain water, which in turn influences the texture and mouth feel characteristics of foods and food products, like comminuted meats, extenders or analogues, and baked dough (Adebowale, Adeyemi, & Oshodi, 2005).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The highest WAC values were found at pH 2 (3.01 cm 3 H 2 O/g protein) and pH 10 (1.71 cm 3 H 2 O/g protein). At neutral pH, WAC was equal to 1.68 cm 3 H 2 O/g protein, higher than that of L. angustifolius protein isolates (0.24 to 0.45 cm 3 H 2 O/g protein) (Lqari et al, 2002) and lower than that of protein isolated from defatted cashew nut shell (2.56 cm 3 H 2 O/g protein) (Yuliana et al, 2014). WAC is an index of the ability of proteins to absorb and retain water, which in turn influences the texture and mouth feel characteristics of foods and food products, like comminuted meats, extenders or analogues, and baked dough (Adebowale, Adeyemi, & Oshodi, 2005).…”
Section: Resultsmentioning
confidence: 74%
“…Thus, at pI the repulsive forces of proteins are weak, favoring droplets emulsion coalescence and hence a poor emulsifying stability. On the contrary, when the electrical charge around oil droplets is high, repulsion forces help maintaining droplet repulsion and retarding emulsion coalescence (Yuliana et al, 2014). Although the highest EC value for LPIA (61.91%) is lower than that for soy protein isolate (74.7%), as an emulsifier, LPIA formed more thermally-stable emulsions than soy protein isolate (73.2%), except at pI (Franzen & Kinsella, 1976).…”
Section: Influence Of Ph On Functional Properties Of the Proteinsmentioning
confidence: 95%
See 1 more Smart Citation
“…The foam stability (FS) was evaluated by measuring the total volume after 2 hour of the foam formation and was calculated according to Yuliana et al (2014) using equation (3).…”
Section: Determination Of Foaming Capacity and Foam Stabilitymentioning
confidence: 99%
“…These values are in agreement with the value reported by Atuonwu and Akobundun [52] for pumpkin seed protein isolate (2.0%). Lawal et al [53] and Yuliana et al [54] also reported that lower least gelation capacity gave better gelation capacity and increase in ionic strength enhances gelation properties. The slight difference in gelation concentration of the defatted flour and isolates may be ascribed to the relative ratios of different constituents such as proteins, carbohydrates, and lipids that make up the flours and also the interactions between such components.…”
Section: Emulsion Capacity (Ec) Of Defatted Unroasted γ-Irradiated Grmentioning
confidence: 97%